Significado niilista de ideais ascéticos no pensamento de Friedrich Nietzsche - Cantalice, Gizolene de Fátima Barbosa da Silva (2015)
This work aims to understand what the philosopher Friedrich Nietzsche calls the ascetic ideals and nihilism. This dissertation is the result of a research that tries to show it specifically from the work On the Genealogy of Morals. The following is an attempt to identify and characterize this issue in other works of this thinker and in the works of some Nietzsche‟s experts. The study begins with an overview of the meaning of ascetic ideals down the forms of expression in the world, through religion, philosophy and art. It presents the ascetic priest as the element from which you get the main understanding of the ascetic ideal; seeks to indicate that talk of the ascetic ideal in the priest‟s talk about how to be critical of the ascetic ideal. On the Genealogy of Morals, the ascetic ideals are characterized as being essentially form of nihilism. We resort to Nietzschean nihilism to show that and how the character will to nothingness intrinsic to nihilism is also present in the ascetic ideal as a form of decay. The conclusion is based on that fact that the ascetic ideals make the decadent will to power because make a will to value where value in this case is the value of nothing. Finally is used to understand the concept of creation as a possibility for overcoming these ideals through tragic art and lawmaker philosophy as a way of will to power.